How to measure flexibility – Performance indicators for demand driven power generation from biogas plants. (April 2019) - Dotzauer, Martin; Pfeiffer, Diana; Lauer, Markus; Pohl, Marcel; Mauky, Eric; Bär, Katharina; Sonnleitner, Matthias; Zörner, Wilfried; Hudde, Jessica; Schwarz, Björn; Faßauer, Burkhardt; Dahmen, Markus; et al.
Abstract: Flexible power provision from biogas can significantly contribute to energy systems with high shares of renewables. However, the characteristics and demands for this flexibility are not clearly defined or measured. In this paper eight indicators are defined to shape "flexibility" and perform a downstream investigation of eight research projects focusing on flexible energy provision of biogas plants. The indicators are structured in three dimensions (1) velocity (ramps) by which the system can be modulated, (2) power range (bandwidth) and (3) duration for specific load conditions. Based on these indicators bottlenecks for the flexibility potential were identified. One crucial result shows that short-term flexibility of biogas plants is mainly driven by properties of the combined heat and power unit (velocity and bandwidth). The long-term flexibility depends mainly on gas storage, mode of operation and ability for modulation of the target gas production. Highlights: Development of eight indicators to measure flexibility performance of biogas plants. Application of flexibility indicators to nine research projects. Sensitivity analysis for flexibility indicators based on a simulated biogas plant. Interpreting and explaining interactions of flexibility factors and the developed indicators. Identifying bottlenecks and trade-off for flexibilization of biogas plants.